The reformasi of Ayu Utami; Attacking the monopoly of the great religions - Steenbrink, Karel (Wacana, Journal of the Humanities of Indonesia, 2014)
In eight novels, Ayu Utami has presented critical attacks on doctrines and practices of the major religions in Indonesia. The two books, that describe the spiritual struggle of the Catholic priest Saman (1998-2002), call for a religion that is more active in the political arena, but leaves sexual rules to the individual people. The novel Bilangan Fu (2008) condemns the monopoly of the great religions in favour of local and individual spirituality. This is developed in a series of novels of which two more have already appeared. A third cycle of three more or less autobiographic novels (2003-2013) sketch her personal quest from atheism towards a critical but positive spirituality condemning a clerical and monopolist trend in Catholicism. Utami's criticism of the great religions is external (more players in the field should be recognised) and internal (religious leaders should have more modest claims towards their faithful and leave more space for personal choice).